Potential Uses of Cord Blood in Cardiac Surgery. (7th March 2012) - Mosca, Ralph S.
Abstract : Despite advances in the fields of prevention, medical intervention and surgical therapy, cardiovascular disease remains a major public healthcare issue. A promising area of research is the potential application of regenerative therapies with pluripotential stem cells to reduce the burden of heart disease and its sequelae. Umbilical cord blood, a rich source of multiple populations of nonembryonic stem cells, will be a valuable resource and has the potential to advance therapeutic options for patients with acquired and congenital heart disease.